TO IMPROVE STUDENTS’ READING COMPREHENSION SKILLS THROUGH WEB-BASED LEARNING PROGRAM - Ganiev A; Alimuradova F (Scholar Express Journal, 2025)
The article gives the information about the attitudes and beliefs of the learners, as well as their reading skills. The article discusses and highlights the use of web-based reading programs, their effectiveness and explores the relationship between independent variables (reading motivation, individual learning styles) and the dependent variable. Recent research indicates that the utilization of web-based teaching approach and the application of stimulating instructional practices not only promote learning interest, but also arouse students’ learning motivation
Keywords: arouse; learning; attitudes